Запиши ответы Раскрой скобки и упрости выражения.

a)n + (n + 5) + (n + 8) =

(n - 5) + (n - 3) + (n + 4)

(n - 2) + (n - 9) + 2n + (n + 8) =

6)(p - 8) - (p + 8) = p - 8 - - 8 =

(p + 12) - (p - 12) =

- (p - 7) + (p + 7) =


Запиши ответы Раскрой скобки и упрости выражения.a)n + (n + 5) + (n + 8) =(n - 5) + (n - 3) + (n + 4

Mawa1993 Mawa1993    1   23.11.2020 12:59    1

Ответы
LizaZay LizaZay  23.12.2020 12:59

n+n+5+n+8=3n+13\\n-5+n-3+n+4=3n-4\\n-2+n-9+2n+n+8=5n-3\\p-8-p-8=-16\\p+12-p+12=24\\p-p+7+p+7=p+14

Объяснение:

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра